Enhancing Patient Services: Transforming a Student-Run Physical Therapy Pro-Bono Clinic - Herbert, Wendy; White, Alana; Schock, Alexis (Journal of Student-Run Clinics, 2025)
Background: Doctor of Physical Therapy (DPT) students at The University of South Florida provide pro-bono physical therapy services to the university area’s underserved community. Annual student leadership turnover and weekly rotation of students and clinical preceptors disrupted continuity of care, prompting student leaders to initiate a program improvement effort. Methods: An iterative quality improvement process guided by input from DPT faculty, alumni, and students informed program changes. Anonymous electronic surveys with ordinal-scale and open-ended questions were distributed at three time points to assess participation barriers, care delivery, and the impact of program changes. Survey results guided adjustments to leadership and treatment team structure and communication strategies. Results: In the initial survey, participants reported lack of preparation, unclear expectations, inadequate communication, and inconsistent care continuity were key barriers. In response, leadership and treatment teams were restructured, incorporating a peer-assisted learning model. A follow-up survey showed that 68% of students and 100% of preceptors perceived improved care continuity. Survey responses also noted a continued need to improve goal setting, documentation, and communication. A centralized communication hub and standardized documentation templates were introduced to address these challenges. Final survey results indicated students valued hands-on experience and peer-assisted learning, reporting increased self-confidence and perceived care continuity. Remaining challenges identified by both students and preceptors included goal alignment and treatment team collaboration. Conclusions: Participant survey responses suggest perceived improvements in care quality and operational efficiency following the restructuring. The central insight from this project is that intentionally redefining roles and implementing a peer-assisted learning model across leadership and treatment teams enhanced clarity, collaboration, and student ownership. These findings support the value of peer-assisted learning models in student-run clinics. Ongoing efforts aim to strengthen this model to improve clinic operations while expanding interdisciplinary collaborations and PT services for the underserved populations.